ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP AUDIT DELAY PADA PERUSAHAAN PERBANKAN - Selly Puspita Sari, 09.05.52.0196; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2013)
This study aims to identify and analyzethe effect of the level of profitability, firm size, Non Performing Loan, Loan to Deposit Ratio, and the external auditors of the Audit Delay banking companies listed in Indonesia Stock Exchange.Its population is banking companies listed in Indonesia Stock Exchange in 2008-2011, the samples taken in this study were 27 companies, and the sampling technique used was purposive random sampling. The method of analysis used in this study is the Multiple Linear Regression Analysis. The analysis tool used was SPSS.The results of this study to test the F-test statistics showed that between independen variables jointly affect the Audit Delay. From the results of hypothesis testing showed that Non Performing Loan has a significant Positive effect, Loan to Deposit Ratio has a significant negative effect. while the firm size, variable profitability, and external auditors variables have a negative impact, but not significant.Keywords: Audit Delay, profitability, firm size, external auditors, Non Performing Loan, Loan to Deposit Ratio.